Analysis of The Marketing Efficiency of Curcuma in The Medicine Plant Processing Industry - Himmatul Miftah; Siti Malihatul Aviah; Syaima Lailatul Mubarokah; Ita Novita; Ikhsan Qodri Pramartaa (Universitas Djuanda, 2023)
Farmers distribute curcuma through several marketing agencies to the sringanis plantation processing industry. It impacts farmers' income, so the research aims to determine the pattern of Curcuma marketing channels as a raw material for the medicinal plant processing industry, the value of efficiency indicators, and the level of efficiency of each marketing channel—methods of data collection using purposive sampling and snowball sampling. Respondents are farmers, middlemen, and managers of the sringanis plantation processing industry. The analytical approach uses quantitative analysis, namely analysis of marketing channels, marketing margins, farmer share, and marketing efficiency. The results showed that there were two patterns of Curcuma marketing channels, namely marketing Channel I, which included farmers and the sringanis plantation processing industry, and marketing Channel II which had farmers, intermediaries, wholesalers, and the sringanis processing industry. The marketing functions performed by all marketing agencies are exchange functions, physical functions, and facility functions. Farmer share obtained by marketing Channel I is more significant than Channel II, so marketing Channel I is more efficient than Channel II. The implication that farmers and the sringanis garden industry can apply is to enter into a cooperation contract where every profit and risk obtained has been adjusted by mutual agreement. Distance constraints for farmers who use marketing Channel II can be overcome by selling a portion of Curcuma produce to intermediaries with a proportion of 60%, and the remaining 30% is sold directly to the sringanis plantation processing industry.